Avaliação da capacidade funcional na cardiopatia chagásica pelo incremental Shuttle Walk Test e sua relação com qualidade de vida - Henrique Silveira Costa (2013)
Background: The Cardiopulmonary exercise test (CPET) is considered to be the gold standard to evaluate functional capacity (FC) in patients with heart failure (HF). However, field tests such as the Six-minute Walk Test (6MWT) and the Incremental Shuttle Walk Test (ISWT) are simple and effective in evaluating the same. Despite the increasing use of ISWT, no studies that used the test in patients with Chagas heart disease (CHD) were found and only few studies have evaluated the health-related quality of life (HRQoL) in this population. Objectives: To correlate the distance walked in the ISWT with distance walked by 6MWT and peak oxygen uptake (VO2peak) by CPET and health-related quality of life (HRQoL) in patients with CHD. Methods: Thirty five patients with CHD were evaluated according to the CF and HRQoL. The CF was assessed by CPET, 6MWT and ISWT. HRQoL was assessed by the generic Short-Form Health Survey (SF-36) and Minnesota Living with Heart Failure Questionnaire (MLHFQ). Descriptive data were shown as mean and standard deviation or median and interquartile range. The correlation was carried out with Pearson or Spearman correlation test. A ROC curve was constructed to investigate the accuracy of ISWT for predicting low values of VO2peak. Results: The distance walked in ISWT correlated with VO2peak (r= 0.498; p= 0.004), distance walked in 6MWT (r= 0.484; p= 0.003), MLWHFQ scores (r= -0.460; p= 0.006) and physical functioning and role physical domains of the SF-36 scores (r= 0.435, p= 0.009; r= 0.477, p= 0.008, respectively). There was no significant difference between the distances walked in field tests (p= 0.694). The area under the ROC curve was 0.871 for ISWT in predicts a VO2peak value of, at least, 25 mL.kg.min. Conclusion: The ISWT showed to be effective in evaluating the FC in CHD and in demonstrate the impact of disease on HRQoL of these patients.